Effectiveness of cognitive behavioural therapy on sleep outcome for patients with chronic fatigue syndrome in a routine clinical service - Chotiman Chinvararak; Olivia Sterry; Trudie Chalder (Europe’s Journal of Psychology, 2026)
Objective We aimed to study the effectiveness of CBT for sleep difficulties in patients with chronic fatigue syndrome/myalgic encephalitis (CFS/ME). Method We conducted a retrospective cohort study at the Persistent Physical Symptoms Research and Treatment Unit, Maudsley Hospital, between 2014 and 2019. The primary outcome was sleep quality and other sleep parameters assessed by the Pittsburgh Sleep Quality Index (PSQI). The secondary assessments comprised the Chalder Fatigue Questionnaire (CFS), the Work and Social Adjustment Scale (WSAS), and the Short-Form Health Survey (SF-36). The data were gathered at baseline, discharge, and follow-up periods (3, 6, and 12 months). A paired samples t-test, repeated measures ANOVAs, and the Friedman Test were used to determine the effectiveness of CBT. A linear mixed model was employed to evaluate the effect size of CBT. Results From all 217 participants (71.4% female; mean age = 39.42 ± 12.32 years), 85.7% experienced poor sleep quality. The associated factors of poor sleep quality at baseline included primary education/secondary education/vocational qualification (OR adj = 3.74, 95% CI [1.03, 13.64], p = .046), CFS score (OR adj = 1.08, 95% CI [1.02, 1.15], p = .015), SF-36 score (OR adj = 0.98, 95% CI [0.96, 0.99], p = .015), WSAS score (OR adj = 1.06, 95% CI [1.02, 1.11], p = .004) and HADS-A score (OR adj = 0.80, 95% CI [0.69, 0.93], p = .004). CBT had a substantial positive effect on sleep parameters, fatigue, and physical functioning over a 12-month follow-up period ( p < .05). Conclusion CBT had a significant positive effect on the sleep parameters. This effect persisted during a 12-month follow-up period. The results suggest CBT is an effective treatment for CFS/ME patients with sleep problems.